PENGARUH PENGGUNAAN MULTIMEDIA SMART TV TERHADAP KEAKTIFAN BELAJAR SOSIOLOGI SISWA SMA NEGERI 3 BULUKUMBA - Torro, Supriadi; Irwansyah, Idham; Aini, Syarifah (Universitas Hamzanwadi, 2023)
The purpose of this study is to find out: 1) Overview of smart TV multimedia learning media in the field of sociology studies at UPT SMA Negeri 3 Bulukumba. 2) Overview of student learning activity in the field of sociology at UPT SMA Negeri 3 Bulukumba. 3) The influence of the use of smart TV multimedia media on student learning activity in the field of sociology studies at UPT SMA Negeri 3 Bulukumba. This study used a type of quantitative research with a descriptive approach, the total population in this study was 126 people. The process of determining the sample size using propability sampling techniques, namely proportionate stratified random sampling which is determined through the Slovin formula and obtained a sample number of 97 people. Data collection techniques in the form of questionnaires and documentation. Validity test using Bivariate Person correlation technique and reliability test using Alpha Cronbach. Data analysis techniques use descriptive statistics and inferential statistical analysis through the help of IBM SPSS Statistics application version 25 for Windows.The results of this study show that: 1) The description of multimedia smart TV learning media in the field of sociology studies at UPT SMA Negeri 3 Bulukumba is in the